Transnationalism and place attachment: sustainable campus planning towards the establishment of global educational hub - Mat Raschid, Mohammad Yazah; Yunos, Mohd Yazid; Fetami, Ezaz (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
Malaysia fundamentally needs to understand the adjustment problems faced by increasing international students’ enrollments in its inspiration to become a premier international education hub. This can be facilitated with the right kind of support by enhancing sense of place attachment amongst the transnationals. The physical planning of Universiti Putra Malaysia (UPM) main campus is outspread due to its large area and seems to contribute to the lack of social interactions and attachment to the university that can assist in improving their campus lifestyles. The aim of this study is investigate the international students’ perception of current place attachment in UPM. A5-points Likert-scaled questionnaire survey on 146 UPM international students and data analysis using SPSS were conducted. Results demonstrate that the tangible physical planning of UPM campus influenced international students’ level of place attachment towards the campus surroundings and their positive lifestyles. However, more improvements to the current planning to enhance social interactions, safety and human comfort are needed to enhance the place attachments in the planning process.